(3EVGAI GdQGehS aj EaGVI GdfGehS Ydi EaGVI GdbGehSs - (3GdaGSj, eMeO Hf ehSi, J(B1170(3g`s
(3ChdgG (B:s
(3bdJ(B: (3CHOdJ GdQGA ef GddGe aj GdfKQI HeYfi GdfKdI hgh GdOQY HOdjd bhdge (B/ (3fKd OQYg Ydjgs
(3BNQgG (B:s
(3hjefMfj KeQI COYjJge GdUGdMI Efg Ydi cd TjA bOjQ Je HMeO Gddg hYhfg hMSf Jhajbg Ydi GdJeGe hGdceGd hGdMeO ddg Ydi cd MGd hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSdes
(3aj BNQgG JGQjN hgh SfI (B1175(3g` , hdG JhLO ETGQI Edi Cfg JGQjN GdfSNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 3 / 374s
(3gOjI GdYGQajf(B: 2 / 331s
(3EjVGM Gdecfhf(B: 1 / 94s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs